Pembakaran Al-Quran Di Swedia Dan Politik Identitas: Islamophobia Atau Kebebasan Berpendapat - Janah, Faidatul (Ri'ayah: Jurnal Sosial dan Keagamaan, 2024)
This paper departs from the problem based on public perception of the burning of the Koran in Sweden by an anti-Islamic politician and activist. The method used is Library Research based on discourse and phenomena that are happening with the type of research that is qualitative. The results of the discussion found in this study are 1) The polemic between freedom of speech and the phenomenon of Islamophobia influenced by identity politics provides different perspectives. The author argues that this action aims to maintain political power by using his identity to be free in voicing his opinion. 2) Islamophobia has implications for political problems because it shows a violation in conveying public opinion that has used religious symbols. The statement is also supported on the basis of the identity that Rasmus Paludan has so far perpetuated the anti-Muslim image